Piezoelectric as an alternative energy source for smart cities: - Isaque Daniel Chaves; Angélica Duarte Lima; Fabiane Florencio de Souza; João Luiz Kovaleski; Regina Negri Pagani (Exacta)
Electricity is fundamental for the development of cities, but at the same time, it represents one of the biggest costs. In this scenario of intense use of electric energy, whose supply can be one of the biggest bottlenecks for industries, piezoelectric emerges as an alternative for energy generation and creation of autonomous systems in different spaces, such as highways, sidewalks, parks, and other public spaces, enabling the implementation of the guidelines of a smart city. The objective of this work is to explore the characteristics of this energy source. Therefore, a systematic literature review was carried out using the Methodi Ordinatio methodology. The results show that piezoelectric materials contribute to urban improvement, sustainability, real-time monitoring, health areas, population comfort, urban mobility, and numerous other areas that can help make a city smarter.